Adiponectin in Cardiovascular Inflammation and Obesity - Tamar R. Aprahamian; Flora Sam (Hindawi Limited, 2011)
Inflammation is widely known to play a key role in the development and progression of cardiovascular diseases. It is becoming increasingly evident that obesity is linked to many proinflammatory and obesity-associated cardiovascular conditions (e.g., metabolic syndrome, acute coronary syndrome, and congestive heart failure). It has been observed that adipokines play an increasingly large role in systemic and local inflammation. Therefore, adipose tissue may have a more important role than previously thought in the pathogenesis of several disease types. This review explores the recently described role of adiponectin as an immunomodulatory factor and how it intersects with the inflammation associated with both cardiovascular and autoimmune pathologies.